2017
DOI: 10.1117/1.jbo.22.3.036009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast wavelength multiplexed broad bandwidth digital diffuse optical spectroscopy for in vivo extraction of tissue optical properties

Abstract: , "Ultrafast wavelength multiplexed broad bandwidth digital diffuse optical spectroscopy for in vivo extraction of tissue optical properties," J. Biomed. Opt. Abstract. Frequency-domain diffuse optical spectroscopy (FD-DOS) utilizes intensity-modulated light to characterize optical scattering and absorption in thick tissue. Previous FD-DOS systems have been limited by large device footprints, complex electronics, high costs, and limited acquisition speeds, all of which complicate access to patients in the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…1(a). This hardware is described in detail in our previous publication [16]. Briefly, five near infrared lasers (690, 785, 808, 830, and 850 nm) were modulated at different radio frequencies using five direct digital synthesis boards (DDS) controlled by a single board computer (MircoZed Zynq-7010 SOC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1(a). This hardware is described in detail in our previous publication [16]. Briefly, five near infrared lasers (690, 785, 808, 830, and 850 nm) were modulated at different radio frequencies using five direct digital synthesis boards (DDS) controlled by a single board computer (MircoZed Zynq-7010 SOC).…”
Section: Methodsmentioning
confidence: 99%
“…Aliasing did not lead to any loss of information in this case because the laser modulation frequencies always mapped to unique and non-overlapping frequencies in the baseband. Since the modulated signals are narrow-band with known frequencies, the amplitude and phase could be extracted from the undersampled signals [16]. While theoretically only one modulation frequency is necessary to separate absorption from scattering [17], other groups have found that using multiple frequencies resulted in measurements that were less susceptible to noise [15,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in FD-NIRS instrumentation include implementations based on a compact frequency-sweeping circuit board (No et al, 2008), digital heterodyning (Arnesano et al, 2012), direct digital sampling (Roblyer et al, 2013;Zimmermann et al, 2016), frequency division multiplexing (Torjesen et al, 2017;Zhao et al, 2018), CMOS integrated circuitry (Sthalekar and Joyner Koomson, 2013;Yun and Joyner Koomson, 2013), and vertical cavity surface emitting lasers (VCSEL) (Sultan et al, 2013;Kitsmiller et al, 2018).…”
Section: Instrumentation For Fd-nirsmentioning
confidence: 99%
“…Optical imaging methods capable of providing real-time information related to functional and structural conditions of living tissues are becoming increasingly popular. [1][2][3][4][5][6] Some medical fields in particular, such as surgery, are driving this need for realtime interpretable information content to aid decision-making in a time-constrained environment. [7][8][9][10][11][12] Several solutions have been investigated to fulfill this need, each with their pros and cons, ranging from raster scanning of microscopic information to wide-field acquisitions of diffused information.…”
Section: Introductionmentioning
confidence: 99%